DESAIN TATA LETAK SIRKUIT TERPADU DALAM PERSPEKTIF PERBANDINGAN HUKUM INTEREN - Sudjana, Sudjana (Veritas et Justitia, 2017)
The author discusses the legal protection of integrated circuit layout design as provided by Law 32/2000 and compares it with how the government regulates and protect other sorts of intellectual property rights (copyright, trademarks, patents, etc.). The purpose of this comparison is to reveal shortcomings as well as the strength of each different regulations. This study reveals that Law 32/2000 as compared to other IPR protections has yet to provide legal protection of inventor’s moral rights, priority rights as well as temporary decision.  At the same time, all regulations cannot be fully implemented due to the lack of or insufficient implementing regulations.